Political And Health Influences On Demand Indonesian Tourism - Andaru Rachmaning Dias Prayitno (Universitas Udayana, 2025)
Tourism demand is one measure of the success of tourism development. The novelty in this studyis that it uses political, health and macroeconomic variables on Indonesian tourism demand fromthe five countries with the highest market share in Indonesia, namely Malaysia, China, Singapore,Australia, Timor Leste and the five countries. This research uses multiple regression and panelregression research methods. The results of this research show that the income of tourists fromChina, Australia, Timor Leste and these five countries has a positive effect on tourism demand,while the income of tourists from Malaysia and Singapore has a positive effect on tourism demand.The exchange rate of tourists from Malaysia, Singapore, Australia, Timor Leste and these fivecountries has a positive effect on tourism demand, while the exchange rate of tourists from Chinahas no effect on tourism demand. Political events have a negative impact on tourists from Australia,a positive impact on tourists from these five countries, and have no effect on tourists from Malaysia,China, Singapore and Timor Leste. Health has a negative effect on tourists from Malaysia, China,Timor Leste and these five countries, while the health of tourists from Singapore and Australia hasno effect on tourism demand.